The possible dual role of Ang-2 in the prognosis of pancreatic cancer - Roos-Mattila Matilda; Kaprio Tuomas; Mustonen Harri; Hagström Jaana; Saharinen Pipsa; Haglund Caj; Seppänen Hanna (Nature Research, 2025)
Pancreatic ductal adenocarcinoma (PDAC) features a dense desmoplastic stroma, which raises the intratumoral interstitial pressure leading to vascular collapse and hypoxia, inducing angiogenesis. Vascular growth factors, such as vascular endothelial growth factor (VEGF) and angiopoietin-2 (Ang-2), increase in PDAC. A high VEGF and a high circulating Ang-2 associate with shorter survival in PDAC. In addition to the circulatory Ang-2, PDAC endothelial and epithelial cells express Ang-2. No correlation between tumor epithelial nor endothelial cell Ang-2 expression and survival has been published. We aimed to examine Ang-2 expression and survival. This study comprised PDAC surgical patients at Helsinki University Hospital in 2000–2013. Ang-2 immunohistochemistry staining was completed on 168 PDAC patient samples. Circulating Ang-2 levels were measured using ELISA in the sera of 196 patients. Ang-2 levels were assessed against clinical data and patient outcomes. A low tumor epithelial Ang-2 expression predicted shorter disease-specific survival (DSS) compared with a high expression (p = 0.003). A high serum Ang-2 associated with shorter DSS compared with a low circulating Ang-2 (p = 0.016). Ang-2 seemingly plays a dual role in PDAC survival. Further studies are needed to determine the mechanisms causing tumor cell Ang-2 expression and its positive association with survival.